The impact of reminiscent music therapy and robot-assisted rehabilitation on older stroke patients: a protocol for a randomized controlled trial - Liu, Qian; Liu, Zuoyan; Cheng, Hong; Xu, Yang; Wang, Fang; Liu, Li; Hu, Xiuying (Frontiers in Neurology, 2024)
Background Stroke is the main disease that causes the burden of neurological disease, leading to upper limb dysfunction and affecting their self-care abilities. Robot-assisted rehabilitation therapy has been gradually used in the rehabilitation of upper limb function after stroke. However, it would be beneficial to explore auxiliary interventions such as reminiscent music therapy, a combination of music and reminiscent, to relieve negative emotions and post-stroke fatigue and improve rehabilitation outcomes. This protocol aims to evaluate the effectiveness of reminiscent music therapy combined with robot-assisted rehabilitation in older stroke patients. Methods This trial is a single-blind, three-arm randomized controlled trial. Older stroke patients with upper limb dysfunction will be recruited. Participants will be randomly assigned to receive usual rehabilitation treatment and care, usual rehabilitation treatment and care plus robot-assisted rehabilitation and reminiscent music therapy, or usual rehabilitation treatment and care plus robot-assisted rehabilitation. Robot-assisted rehabilitation will be conducted by rehabilitation doctors five times per week for 3 weeks. In experimental group 1, a reminiscent song list will be played for patients. The primary outcome is activities of daily living. All outcomes will be evaluated at baseline and in the week immediately post-intervention. Discussion We are conducting the first randomized controlled trial on the effects of reminiscent music therapy combined with robot-assisted rehabilitation in older stroke patients. It is expected that this study, if proven effective in improving the activities of daily living in older stroke patients with upper limb dysfunction, will provide evidence-based rehabilitation strategies for medical staff. Clinical Trial Registration: ChiCTR2200063738.